Service quality attributes influencing spa goers’ satisfaction in Kuala Lumpur, Malaysia / Ameleya Muhammad Ghazali ... [et al.] - Muhammad Ghazali, Ameleya; Abdul Latip, Muhammad Safuan; Zulkurnain, Muhammad Zulhilmi; Zainozaman, Mohammad Syakir (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
Wellness Tourism has become a booming niche product of tourism. The Malaysian government views the spa industry as a catalyst to boost the economy. Somehow, the empirical study on the satisfaction of spa-goers specifically in Malaysia is limited to knowing which service quality attributes can help the spa owners focus on and sustain the business. Thus, this study aims to examine the relationship the service quality attributes to spa-goers satisfaction as a catalyst to help the spa owners to improve the business according to spa-goers’ expectations. An empirical study was conducted with 365 spa-goers ranging from 18 years and above who have enjoyed any services in spa centres in Kuala Lumpur. Self-administered questionnaires were given at 59 spas registered under the Ministry of Tourism and Culture. Data analysis was performed using SPSS and PLS-SEM. Resultantly, service quality attributes ’ reliability, empathy, and assurance of spa providers positively affect the spa-goers satisfaction when choosing a spa centre. This study provides spa owners to re-formulate the strategies to retain their customers and be sustained in the spa industry. However, this study is limited as the findings were based on spa centres located only in Kuala Lumpur only, Thus, the study can be replicated as future research in other states for a wider and comprehensive understanding of spa-goers and it will expand the knowledge in the spa industry.